2002
DOI: 10.1080/003655202317284309
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Hepatic Failure After Emergence of the Hepatitis B Virus Mutant During Lamivudine Therapy in a Patient with Liver Cirrhosis

Abstract: Lamivudine therapy for chronic hepatitis and decompensated liver cirrhosis related to the hepatitis B virus (HBV) resulted in improvement of liver function and inhibition of viral replication. Despite emergence of the HBV mutant, e-antigen seroconversion and improvement of liver function may be achieved with continuation of lamivudine therapy. Although hepatic decompensation has been reported in a few cases after the emergence of lamivudine-resistant mutants, fatal cases of non-transplant patients have only ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…4,5 Viral breakthrough associated with selection of antiviral-resistant hepatitis B virus (HBV) mutants is usually followed by biochemical breakthrough and in some instances hepatitis flares and liver failure. [6][7][8][9][10] Therefore, treatment should be changed when viral breakthrough is detected. However, multi-drug resistant HBV has been reported in patients who received sequential treatment with NA monotherapies.…”
mentioning
confidence: 99%
“…4,5 Viral breakthrough associated with selection of antiviral-resistant hepatitis B virus (HBV) mutants is usually followed by biochemical breakthrough and in some instances hepatitis flares and liver failure. [6][7][8][9][10] Therefore, treatment should be changed when viral breakthrough is detected. However, multi-drug resistant HBV has been reported in patients who received sequential treatment with NA monotherapies.…”
mentioning
confidence: 99%
“…However, long-term therapy is associated with selection of HBV polymerase mutants and emergence of resistance (7,11,14,15,33). Resistance to antiviral treatment (including lamivudine) has Various methods have been used to detect YMDD mutant populations of viruses (among others, nested PCR, cloning, and sequence analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has also indicated that in northern China, the YMDD mutation rate is approximate 56.3% after four years of lamivudine treatment [8] . YMDD mutations not only result in a reduction in the susceptibility to lamivudine, but also cause virological and biochemical breakthrough, which are represented as rebound of HBV DNA and ALT levels [19,20] . Moreover, acute exacerbation of hepatitis and hepatic failure may occur after the emergence of YMDD mutants.…”
Section: Discussionmentioning
confidence: 99%